Development and Validation of Molecularly Imprinted Polymers with Bio-Based Monomers to Adsorb Carbamazepine from Wastewater - Elettra Savigni; Elisa Girometti; Laura Sisti; Frank Benstoem; Davide Pinelli; Dario Frascari (Molecules, 2025)
The removal of pharmaceutical contaminants like the anticonvulsant carbamazepine (CBZ) from water sources is a growing environmental challenge. This study explores the development of molecularly imprinted polymers (MIPs) tailored for CBZ adsorption using a bulk polymerization approach. Initially, this study focused on selecting the optimal cross-linker, comparing a trifunctional (trimethylolpropane triacrylate, TRIM) and a bifunctional cross-linker (ethylene glycol dimethacrylate, EGDMA) in combination with two common monomers (2-vinylpyridine and methacrylic acid). TRIM-based MIPs demonstrated superior adsorption efficiency and stability due to their higher cross-linking density. To improve sustainability, six bio-based monomers were investigated; of these, eugenol (EUG) and coumaric acid (COU) showed the best CBZ affinity due to π-π interactions and hydrogen bonding. Adsorption tests conducted in pharmaceutical-spiked real wastewater demonstrated that MIPs exhibit a high selectivity for CBZ over other pharmaceuticals like the anti-inflammatory drugs diclofenac (DCF) and ibuprofen (IBU), even at high concentrations. Reaction conditions were further optimized by adjusting the reaction time and the ratio between reagents to enhance selectivity and adsorption performance. These results highlight the potential of bio-based MIPs as efficient and selective materials for the removal of pharmaceutical pollutants from wastewater.